An Overview on Production, Properties, Performance and Emission Analysis of Blends of Biodiesel. (2016) - Madiwale, S.; Bhojwani, V.
Abstract: The steep rise of demand of petroleum based fuel is because of rapid and fast industrialization of automotive sector. There are limited reserves for petroleum based fuels. These limited reserves are located in the certain regions of the world. Therefore the countries those are not having the sufficient stock of petroleum based fuel, are facing the problems of increase cost of fuel which mainly due to the cost involved in the import of the petroleum based fuel. Hence it is required to find out and investigate the other resources of the alternative fuels, which can be produced from nearby and locally available sources such as Alcohol, Biodiesel, Vegetable oil etc. Methyl or ethyl esters of fatty acids produced from vegetable oil or an animal fat is called biodiesel. Non edible oil or animal fats are the main recourses for production of biodiesel such as Jatropha, Palm, Marine fish oil, Soybean, Cottonseed etc. Biodiesel blends are prepared in any proportion with diesel to use in a conventional diesel engine. By using biodiesel in an engine there is a significant reduction in the harmful pollutants in the environment. This paper reviews the production, properties, performance and emission analysis of different feedstock of blends of biodiesel and experimental work carried out in the various parts of the world.